Hubungan Dukungan Keluarga Dengan Tindakan Penanganan gizi Kurang (PBHS) Pada Anak Di Desa Penfui Timur - Puskesmas Tarus – Kabupaten Kupang - Dion, Yohanes; Marthen Laganguru, Henry (NHM PRESS, 2023)
Background: Nutritional problems are complex health problems in people all over the world, especially in people in developing countries such as Indonesia. Undernourished toddlers if not handled properly it will get worse and can become malnourished. During the child's growth and development process, family support is needed to nurture and educate so that the child's growth and development process can run well. Clean and healthy living behavior requires public and household awareness regarding the prevention and handling of nutritional problems or the spread of disease in the community.Objective:This study aims to determine the relationship between family support and actions to handle malnutrition (using the household phbs approach) in children in the East Penfui Village, Tarus Health Center Work Area, Kupang Regency.Methods:This study is a quantitative study using a cross-sectional design and techniques that used for sampling is a total sampling technique with a total sample of 51 respondents. Results:The results of the study showed that: There was a relationship between family support and actions to deal with malnutrition (using the household phbs approach) in children in the East Penfui Village, Tarus Health Center Work Area, Kupang Regency; Suggestion:Through this research, it is hoped that families in dealing with children who are malnourished should continue to support and improve child prevention so that malnutrition does not occur.